KONSTRUKSI PEMBERITAAN MEDIA KONFLIK ISRAEL PALESTINA PADA DETIK.COM DAN TEMPO.CO - Adriel Bigael Lois Saiya; Yunita Indinabila; Suprihatin; I. B. Wirawan (LPPM Stikosa-AWS, 2025)
This study analyzes the construction of news coverage of the Israel–Palestine conflict on the news portals Detik.com and Tempo.co. Using a qualitative descriptive method with Robert N. Entman's framing analysis approach, this study examines four elements of framing: problem definition, cause determination, moral judgment, and resolution recommendations. The research data consists of 20 news articles (10 from Detik.com and 10 from Tempo.co) published between September 10 and October 10, 2024, selected based on their highest readership. The results show that Detik.com tends to emphasize chronological and humanitarian aspects, while Tempo.co emphasizes political and diplomatic analysis. The differences in news coverage reflect the different editorial orientations of each media outlet. This research contributes to understanding how Indonesian online media frame international conflicts and their impact on public perception.